Elective Colorectal Surgery Service Provision during SARS-CoV-2 Pandemic - Cunha, Pedro Oscar R. (Journal of Coloproctology, 2022)
The SARS-Cov-2 pandemic and its immediate public health impact has caused severe disruption of regular medical care provision. The morbimortality of other diseases continues to affect people regardless of the viral infection. Indeed, it would be reasonable to assume that they have been aggravated by the period of most restrictive public health measures that were adopted against the virus. Recovery and maintenance of healthcare provision is required despite the ongoing threat. Therefore, it is critical to resume services in a structured and safe way, otherwise greater harm could come to our patients and to ourselves. The present article proposes to be a broad guide to the recovery and maintenance of elective outpatient, surgical and lower endoscopic services, aiding the colorectal surgeon in identifying risks, assessing their multiple dimensions, and implementing risk management strategies in a pragmatic and efficacious way.
Keywords: pandemic; Covid-19; SARS-Cov-2; colorectal surgery